2012
DOI: 10.3844/ajavsp.2012.7.11
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Vs Tapentadol: Anew Horizon in Pain Treatment?

Abstract: Problem statement: Acute and chronic pain is a common presenting sign in animal species and human beings. Approach: Classical opioids provide very effective pain relief, although they may be less effective in the treatment of chronic pain due to their limited therapeutic windows and the induced opioid receptor down regulation. Atypical opioids, such as tramadol and tapentadol, have a dual mechanism of action and have been designed to overcome these issues through an opiate-sparing effect. Results: Tramadol act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These metabolites of tramadol are more potent than the parent molecule. Since tramadol needs to be metabolized, it generally has a delayed onset of action and less reliable effect in some individuals 3 .…”
Section: Tapentadol Vs Tramadol -Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…These metabolites of tramadol are more potent than the parent molecule. Since tramadol needs to be metabolized, it generally has a delayed onset of action and less reliable effect in some individuals 3 .…”
Section: Tapentadol Vs Tramadol -Pharmacokineticsmentioning
confidence: 99%
“…However, these drugs were created as effective and yet much safer analogues of morphine. Although both the drugs work by influencing opioid receptors (especially mu-opioid receptors or MOR), there is a difference 3 . Activation of MOR receptors results in the potent painkilling effect of opioids.…”
Section: Tapentadol Vs Tramadol -Pharmacodynamicsmentioning
confidence: 99%
“…It is likely that this is associated with the emergence of peripheral analgesic activity of serotonin when the dose is increased. It has been demonstrated that opioidergic mechanisms are also involved at these two levels (supra spinal and peripheral) (Giorgi, 2012). In contrast, MRZ had no antinociceptive activity at the central spinal level (tail clip and flick tests).…”
Section: Introductionmentioning
confidence: 98%
“…In canine species, MRZ orally administered (at about 1 mg kg −1 ) showed a favourable pharmacokinetic profile (which is different to that in both cats and humans) compared to other CNS active drugs such as clomipramine (King et al, 2000), fluoxetine (Simpson et al, 2007) and trazodone (Gruen and Sherman, 2008). For these reasons, it was speculated (Giorgi, 2012) to be potentially useful for veterinary patients for treatment of anorexia and a wide range of anxiety-related conditions (Overall, 2000), for its antiemetic properties (due to antagonism of 5-HT 3 receptor) and as an analgesic in chronic and cancerassociated pain, due to its effects on both the noradrenergic and serotonic system (Bannister et al, 2009). Pharmacokinetics and metabolism have been reported to be largely variable among these species.…”
Section: Introductionmentioning
confidence: 99%